Zinc and Anthropometry in Sickle Cell Disease: Comparison between Two Genotypes (SS and SC Hemoglobinopathies). - Alaka Anuoluwapo Abisola (Journal of Integrated Health Sciences, 2022)
Introduction: Homozygous rather than heterozygous sickle cell disease (SCD) is considered the more severe form of the disorder. While some markers have been used successfully to distinguish between the two with respect to disease severity, the role of other markers remains either inconclusive (e.g., nitric oxide) or ambiguous (e.g., anthropometry). The objective of the study was to provide information about possible variations in anthropometry and zinc (Zn) levels among SS and SC patients in Osun State, Nigeria. Materials and Methods: Adult participants enrolled consisted of 34 SS hemoglobinopathy (also known as HbSS); 32 SC hemoglobinopathy (commonly referred to as HbSC) patients and 32 with HbAA as control. Serum Zn estimation was done by atomic absorption spectrophotometry. Anthropometry (body weight, standing height, body mass index [BMI], head and mid‑upper‑arm circumferences [MUACs]) was determined using standard procedures. Data were analyzed with analysis of variance and Pearson correlation coefficient. P < 0.05 was considered statistically significant. Results: All anthropometric parameters were significantly lower for SCD patients compared with control, but only body weight was significantly different when HbSS and HbSC were compared. Serum Zn status of control was higher than those of SCD patients, with HbSS values being more significantly lower than those of HBSC. Among the HbSS as well as HbSC patients, there was a positive correlation between BMI and Zn as well as between HC and MUAC. Conclusion: Results of the study indicate that while the Zn status of HbSS and HbSC were significantly different, most of the anthropometric parameters were not significantly different.